The Impact of the Content of the Label on the Buying Intention of a Wine Consumer - Escandon-Barbosa, Diana; Rialp-Criado, Josep (Frontiers in Psychology, 2019)
This paper aims to analyze the influence of the content of the label of wine bottles on the purchase intention of wine. The study uses eye tracking to estimate the behavior related to wine attributes included on the label of wine bottles, specifically the denomination of origin, nutritional information, and health warnings. The authors use the hierarchical model methodology, which generates a pattern of relationships among variables. Among the results, it is possible to determine a consistent model for purchase intention, where the mentioned components of the label that are related to wine attributes and their interactions constitute important factors in the possibility of influencing a purchase intention. However, when executing a group division of the audience attending to the experience in wine consumption, it is evident that based on their experience, consumers read the labels’ information differently, causing certain effects in their buying intention.